2015
DOI: 10.1007/978-3-319-19443-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies of Fiber Metal Laminate (FML) Thin-Walled Tubes Under Impact Loading

Abstract: Fiber metal laminate (FML) in form of tubular structures is a modern light-weight structure fabricated by incorporating metallic and composite materials. This present study deals with the impact characteristics and energy absorption performances of fiber metal laminate (FML) thin-walled tubes subjected to impact loading. Dynamic computer simulation techniques validated by experimental testing are used to perform a series of parametric studies of such devices. The study aims at quantifying the crush response an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Ahmad et al 90) studied the crush response and energy absorption capacity of FML thin-walled tubes and compared them with Al and composite tubes. Results indicated that FML tubes were favored as impact energy absorbers because they could sustain greater impact loads, therefore absorbing more energy.…”
Section: Axial Impact Test On Fmlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad et al 90) studied the crush response and energy absorption capacity of FML thin-walled tubes and compared them with Al and composite tubes. Results indicated that FML tubes were favored as impact energy absorbers because they could sustain greater impact loads, therefore absorbing more energy.…”
Section: Axial Impact Test On Fmlsmentioning
confidence: 99%
“…The most tested FML structures were in form of tubes (circular/cylindrical, square). The influence of FML's constituents (composite and metal alloy), fibre orientation, stacking sequence, metal arrangement and laminate thickness played a role in determining the crushing behavior and improving the crush stability and energy absorption of FML structures 41,46,81,[87][88][89][90][91][92]95) . The FML structure had better crushing strength compared to the metal structure [94][95][96] .…”
Section: Axial Impact Test On Fmlsmentioning
confidence: 99%
“…Many researchers have also used hybrid structures that include both types of material, i.e. metallic and composites, to absorb a greater amount of energy such as composite wrapped thin-walled metal tubes or tubes reinforced with externally bonded fibres [9], [8], [10], [11], [12], [13], and [14]. The hybrid structures combine the desirable properties of each material, the high ratio of strength to weight of the composites and ductility and stable plastic deformation mode of the metals [11].…”
Section: Introductionmentioning
confidence: 99%